Use of Bismuth in Irritable Bowel Syndrome - T. A. Ilchishina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2021)
Aim. An evidence review on use of bismuth in irritable bowel syndrome.Key points. Irritable bowel syndrome (IBS) is a common functional disorder significantly impacting the quality of life and social status, i.a., through frequent manifestations of diarrhea. Postinfectious IBS emerges after a bacterial, pro-tozoan or viral intestinal disease. The new coronavirus pandemic supposedly affects most factors involved in functional disorder developments and may serve a fuelling cause of postinfectious IBS. Bismuth salts accumulate cytoprotective, anti-inflammatory and antibacterial properties. Therapeutic efficacy of bismuth compounds has been demonstrated in treatment of diarrhea-accompanied diseases of   various etiology, including postinfectious IBS. The use of therapeutic-dosed bismuth preparations is safe and well tolerated by patients.Conclusion. Use of bismuth may be considered a treatment and prevention approach in diarrhea-predominant IBS, both in monotherapy and combined regimens.